(untitled) (Fiep Bulletin - online, 2011)
The mountain biking is a sport that grows in Brazil and develop elite athletes who are preparing hard for international competitions, requiring scientific information to guide their training optimally, thus reducing the loss of time, money, material and most importantly; the health of the athlete. The city of São Bento do Sul, Santa Catarina in the northern highlands has a relevant national prominence. The topography of the city seems to influence the development of athletes in the sport. The aim of this study was to evaluate the Somatotype, capacity and anaerobic power athletes and the sport of mountain bike from the city of São Bento do Sul-SC. The group was composed of athletes practicing in Mountain Bike, aged (15 and 30 years), all male, resident and domiciled in São Bento do Sul located in Santa Catarina-Brazil. Because of its peculiarities, was taken as a case study. For the Somatotype was used the technique of Heath & Carter (1990); for body fat was used the equation proposed by Faulkner (1968 in Fernandes Filho 2003), to assess the capacity and anaerobic power, the second Wingate test Pompey (2004) and the following equipment: skinfold caliper CESCORF mark, metal anthropometric tape SANNY, caliper blunt WCS, Cardiomed wall mounted, medical Filizola balance and a cycle ergometer with mechanical braking model MONARK. The study group had a mean age of 22.9 ± 5.4 years, with mean weight of 66.7± 6.8kg, while its height was the average of 176.2 ± 4.2cm. and with an average percentage of body fat of 11.7 ± 2.2%. How mean Somatotype find: Endomorphic (2.0±0.6); Mesomorphic (4.1±1.1) and Ectomorphic (3.1±1.3). We conclude that the biotype ideal for mountain bike, based on the findings of the group investigated for better performance generator power and anaerobic capacity is the meso-endomorphic.